1961
DOI: 10.1099/00221287-25-1-103
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Studies of Methanogenesis in the Bovine Rumen: Dissimilation of Acetate

Abstract: SUMMARYThe introduction of sodium acetate-2-14C into a bovine rumen resulted in the in vivo labelling of the rumen gases and volatile fatty acids. The relative isotope concentration in substrate and products indicated that a maximum of 5.6 % of the methane and 11% of the carbon dioxide in rumen gas might have been derived from the methyl carbon of acetate when the substrate was added to the rumen 18 hr. after the animal had been fed a normal ration, A maximum of 3-53 % of the methane and 4.2 % of the carbon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Methane is also produced from acetate via the aceticlastic pathway and this pathway appears to be limited to members of the order Methanosarcinales (Liu and Whitman, 2008). Oppermann et al (1961) measured the increase in radio-labelled methane following infusion of 14 C-acetate in vivo and concluded that this pathway was not important in the rumen. Methanosarcina grown on acetate had a very slow growth rate in vitro suggesting they would not thrive under normal rumen conditions and retention times (Stewart et al, 1997).…”
Section: Rumen Methanogensmentioning
confidence: 99%
“…Methane is also produced from acetate via the aceticlastic pathway and this pathway appears to be limited to members of the order Methanosarcinales (Liu and Whitman, 2008). Oppermann et al (1961) measured the increase in radio-labelled methane following infusion of 14 C-acetate in vivo and concluded that this pathway was not important in the rumen. Methanosarcina grown on acetate had a very slow growth rate in vitro suggesting they would not thrive under normal rumen conditions and retention times (Stewart et al, 1997).…”
Section: Rumen Methanogensmentioning
confidence: 99%
“…In the rumen, feeds can be hydrolyzed by protozoa and bacteria to monomers, subsequently fermented to end products such as volatile fatty acids (VFA), carbon dioxide (CO 2 ) and hydrogen (H 2 ), whereas the end products CO 2 and H 2 can be utilized to produce CH 4 by ruminal methanogenic archaea (Denman et al, 2007;Franzolin et al, 2012). It has been reported that there are several pathways of CH 4 production in the rumen, such as CO 2 reduction, formate oxidation, acetate dissimilation and methanol disportionation to CH 4 (Oppermann et al, 1961;Neumann et al, 1999;Leahy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In digestors, acetate is the major carbon precursor of methane and may account for approximately 70% of the total methane formed (11,19), whereas in lake sediments from 53% (4) to 70% (7) methane may come from acetate. In contrast, only 5.6% of the methane is formed from acetate in the bovine rumen (17). This difference may be attributed to the difference in end-product (i.e., acetate) removal in the rumen versus non-gastrointestinal habitats and/or to the higher turnover of cell material.…”
mentioning
confidence: 95%